Bioavailability, leachability, chemical speciation, and bioremediation of heavy metals in the process of composting - Singh, Jiwan (Professor of environmental science); Kalamdhad, Ajay; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
Currently, it is a serious concern to manage waste in the environment. Therefore, detailed knowledge of heavy metals, their eco-toxicological and health effects and ecofriendly approaches for their immobilization and detoxification is urgently required to control and minimize the environmental pollution. Composting is one of the popular methods in waste management and there are a lot of issues pertaining to composting. One of it is the leaching of heavy metals. This book discusses thoroughly, the availability, leachability and the speciation of heavy metals in the entire process of composting.
chapter 1 Introduction -- chapter 2 Composting Process -- chapter 3 Analysis of Compost Samples -- chapter 4 Composting and Heavy Metals -- chapter 5 Bioavailability of Heavy Metals during Composting -- chapter 6 Chemical Speciation of Heavy Metals during the Composting Process -- chapter 7 Effects of Chemical Amendments on Bioavailability and Fractionation of Heavy Metals in Composting -- chapter 8 Reduction of Bioavailability of Heavy Metals by Microorganisms -- chapter 9 Leachability of Heavy Metals during the Composting Process.
Keywords: SCIENCE / Environmental Science; TECHNOLOGY & ENGINEERING / Agriculture / General; Bioremediation; Compost; Heavy metals; Speciation (Chemistry)